2016
DOI: 10.3892/etm.2016.3301
|View full text |Cite
|
Sign up to set email alerts
|

Treatment effect of cyclosporine A in patients with painful bladder syndrome/interstitial cystitis: A systematic review

Abstract: Cyclosporine A (CyA) is emerging as a potential therapeutic strategy for painful bladder syndrome/interstitial cystitis (PBS/IC), which is currently an incurable disease. The purpose of this systematic review was to evaluate the treatment effects of CyA in PBS/IC. Electronic and manual retrieval procedures were carried out to identify eligible references for the systematic review. The entire contents of the included articles were assessed, from study design to reported results. Eight studies, comprising three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…Cyclophilins are a family of proteins present in vertebrates and other organisms. They bind to CsA, an immunosuppressant that is commonly used to suppress rejection after organ transplantation ( 19 20 ). The molecular mechanisms of CsA-induced β cell apoptosis probably involve the downregulation of cyclophilins.…”
Section: Discussionmentioning
confidence: 99%
“…Cyclophilins are a family of proteins present in vertebrates and other organisms. They bind to CsA, an immunosuppressant that is commonly used to suppress rejection after organ transplantation ( 19 20 ). The molecular mechanisms of CsA-induced β cell apoptosis probably involve the downregulation of cyclophilins.…”
Section: Discussionmentioning
confidence: 99%
“…[182][183][184][185][186] Of note, the benefits of the low-dose cyclosporine A reportedly used must be weighed against side effects such as hypertension and renal function impairment, which appear to resolve after discontinuation, at least in the short term. [186][187][188] The sixth and final line of therapy is more radical surgical treatment such as diversion with or without cystectomy and substitution cystoplasty. Very few patients will ever progress to this level of treatment, but small studies suggest that this can relieve patients of irritative voiding symptoms and particularly may be useful for those with a fixed small bladder capacity.…”
Section: Treatmentmentioning
confidence: 99%
“…The authors concluded that treatment with CyA could potentially result in long-term benefit; however, further evidence is required to confirm these findings. 45 CyA may be dosed at 2 mg/kg divided into twice daily (bid) dosing and drug levels should be monitored. Side effects are common, and patients must be monitored for renal impairment, hepatic impairment, electrolyte abnormalities, hypertension, and infection.…”
Section: Cyclosporine Amentioning
confidence: 99%